DIVAs 4.0: A Multi-Agent Based Simulation Framework - Al-Zinati, M.; Araujo, F.; Kuiper, D.; Valente, J.; Wenkstern, R. Z. (2013 IEEE/ACM 17th International Symposium on Distributed Simulation and Real Time Applications, 2013)
In this paper we present DIVAs 4.0, a framework that supports the development of large-scale agent-based simulation systems where agents are situated in open environments. DIVAs includes high-level abstractions for the definition of agents and open environments, a micro kernel for the management of the simulation workflow, domain-specific libraries for the rapid development of simulations, and reusable, extendable components for the control and visualization of simulations. We illustrate the use of DIVAs through the development of a simple simulator where virtual agents are situated in a virtual city.